Matrine counteracts obesity in mice via inducing adipose thermogenesis by activating HSF1/PGC-1α axis. (March 2022) - Li, Chan; Xu, Yao-Hao; Hu, Yu-Tao; Zhou, Xiu; Huang, Zhi-Shu; Ye, Ji-Ming; Rao, Yong
Abstract: Promoting energy expenditure is known to curb obesity and can be exploited for its treatment. Our previous study has demonstrated that activation of HSF1/PGC-1α axis efficiently induced mitochondrial biogenesis and adaptive oxidation and thus ameliorating lipid accumulation, however, whether it can be a therapeutic approach for metabolic disorders treatment needs explored. Here, a high-efficient and specific HSF1/PGC-1α activator screening system was established and the natural clinical liver-protecting agent matrine was identified as a robust HSF1/PGC-1α activator. Matrine treatment efficiently induced mitogenesis and thermogenic program in primary mouse adipose stem cell derived adipocytes by enriching HSF1 to the promoter of Pgc-1α . Deficiency of PGC-1α in adipocytes diminished the browning induction ability of matrine. Oral administration of matrine to the obese mice induced by high fat and high cholesterol diet increased energy expenditure and corrected the degeneration of thermogenesis in brown adipose tissue (BAT). Also, matrine treatment markedly induced the transformation of brown-like adipocytes in subcutaneous white adipose tissue (sWAT) via a mechanism of HSF1/PGC-1α, thereby attenuating obesity and myriads of metabolic disorders. This led to an improvement in adaptive thermogenesis to cold stimuli. These findings are of great significance in understanding the regulation mechanisms of the HSF1/PGC-1α axis in thermogenesis and providing a novel therapeutic approach for obesity treatment. Matrine may have potential therapeutic implications for the treatment of obesity in clinics. Graphical Abstract: An efficient HSF1-PGC-1α axis activator screening system has been developed. Matrine has been identified as a robust HSF1/PGC-1α activator which may have potential therapeutic implications for the treatment of obesity via inducing adipose thermogenesis. ga1